PENGARUH FLASH SALE, WEBSITE QUALITY DAN PROMOSI GRATIS ONGKIR TERHADAP IMPULSE BUYING DI MARKETPLACE ONLINE SHOPEE - Ari Atrian; Sholihah, Erlinda (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2024)
This study aims to determine the effect of flash sale, website quality and free shipping promotion on impulse buying in the online shopee marketplace. This type of research uses a quantitative approach. This study uses three independent variables, namely flash sale, web quality, and free shipping promotion with one dependent variable, namely Impulse Buying. After being carried out in the library and in the field, and the preparation of hypotheses, the data in this study were collected through the distribution of questionnaires as research samples with a sampling technique using a Likert scale. Process the data through the SmartPLS. The results of this study can be said that 1) Flash sales has a positive and significant effect on impulse buying martkeplace online shopee 2) Website quality has a positive and significant effect on impulse buying martkeplace online shopee 3) free shipping promotion has a positive and significant effect on impulse buying martkeplace online shopee.